Expert Oracle GoldenGate - Prusinski, Ben; Phillips, Steve; Chung, Shing (Apress : Imprint: Apress, 2011)
Expert Oracle GoldenGate is a hands-on guide to creating and managing complex data replication environments using the latest in database replication technology from Oracle. GoldenGate is the future in replication technology from Oracle, and aims to be best-of-breed. GoldenGate supports homogeneous replication between Oracle databases. It supports heterogeneous replication involving other brands such as Microsoft SQL Server and IBM DB2 Universal Server. GoldenGate is high-speed, bidirectional, highly-parallelized, and makes only a light impact on the performance of databases involved in replication. The authors share their experience in the form of tutorials on designing and implementing all types of Oracle GoldenGate environments. You'll learn methods for tuning Oracle GoldenGate performance. You'll discover GoldenGate's utility as a migration and extract, transform, load (ETL) tool. You'll learn to configure highly-available environments involving GoldenGate, Real Application Clusters, and Data Guard. From installation to design to implementation and troubleshooting, Expert Oracle GoldenGate helps you master all aspects of using and applying Oracle GoldenGate as the replication tool of choice in your environment. Explains all aspects of using GoldenGate for replication Covers homogeneous, heterogeneous, and bidirectional replication Shows the use of GoldenGate for data migration and extract, transform, load (ETL).